EXAMINATION OF CASH FLOW FORECASTING KNOWLEDGE AMONG SMALL BUSINESS ENTERPRISES IN ENUGU STATE, NIGERIA - Odo, Samuel N. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The study of the forecasting of future cash flows is essential for detecting deterioration in business financial situations. The study investigated cashflow forecasting knowledge among small enterprises in Enugu state Nigeria. One hundred and seventeen small business enterprises conveniently selected from Enugu state participated in the study. A self-developed instrument was used as a measure. The study adopted a cross-sectional survey design. The result was based on data from 41 (35%) retail businesses, 33 (28.2%) ICT operators, 16 (13.7%) small manufacturing firms, and 27 (23.1) engineering workshops in Enugu state. Data were evaluated using the statistical package for social sciences (SPSS, version 23). A simple percentage formula was used to analyze the data to determine cash flow knowledge among the respondents. The result indicated that 78 respondents representing 66.7% of the total participants, scored high on cash flow knowledge, meaning that they understand cash flow forecasting. The finding suggests that 39, representing 33.3% of the respondents, were not knowledgeable about cash flow forecasting. The result has implications for research and business analysis.